2021
DOI: 10.1371/journal.pone.0259394
|View full text |Cite
|
Sign up to set email alerts
|

Music and low-frequency vibrations for the treatment of chronic musculoskeletal pain in elderly: A pilot study

Abstract: Background Transcutaneous vagal nerve stimulation has analgesic potential and might be elicited by abdominally administered low-frequency vibrations. The objective was to study the safety and effect of a combination of music and abdominally administered low-frequency vibrations on pain intensity in elderly patients with chronic musculoskeletal pain. Methods This trial was an international multicenter, randomized controlled pilot study. Patients at age ≥ 65 years with musculoskeletal pain for ≥ 3 months and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…In this review, we found that studies on acute postoperative and experimentally induced pain (all of them being quasi-experimental studies) describe a decrease in pain sensation over time. However, the differences between experimental and control groups were mostly statistically insignificant (or both groups were significantly improved, such as in Eshuis et al ) 37. Acute pain literature is rather scarce, with small sample sizes and other methodological issues.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…In this review, we found that studies on acute postoperative and experimentally induced pain (all of them being quasi-experimental studies) describe a decrease in pain sensation over time. However, the differences between experimental and control groups were mostly statistically insignificant (or both groups were significantly improved, such as in Eshuis et al ) 37. Acute pain literature is rather scarce, with small sample sizes and other methodological issues.…”
Section: Resultsmentioning
confidence: 98%
“…During the updated search (conducted on 9 January 2022), we found three research studies (one double-blind RCT pilot study,37 one pretest post-test study without a control group,38 one case study)39 and one RCT protocol published at ClinicalTrial.gov. The three studies include participants with chronic pain caused by Ehler-Danlos syndrome,38 postherpetic neuralgia39 and chronic musculoskeletal pain 37.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations